Propylthiouracil induced ANCA positive vasculitis. A case report - Soto Fonseca, Marco Antonio (2021)
ANCA vasculitis associated to propylthiouracil (PTU) is a rare condition with an incidence of 0.47-0.71 cases per 100,000 patients. It affects mainly minor caliber blood vessels. The skin, kidneys and lungs are the organs most affected. To make the diagnosis it is necessary to have a high index of suspicion and rely on histopathologic findings of skin lesions plus a positive ANCA test. Stopping the inducing drug is usually necessary to manage this condition. We report the case of a 45-year-old woman who consumed PTU for two years for the treatment of hyperthyroidism presenting with painful purpuric plaques in the lower limbs.